1976
DOI: 10.1021/jm00231a009
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for biological activity among antileukemic glaucarubolone ester quassinoids

Abstract: A C-15 ester substituent is required for significant antileukemic activity among the glaucarubolone ester quassinoids, and variations in the ester group are not accompanied by particularly marked changes in antileukemic activity. Unsaturation at the 3,4 position is advantageous for optimal activity, and hydrogenation of this double bond results in marked diminution in both cytotoxicity toward KB cells in tissue culture and inhibitory activity against the P-388 lymphocytic leukemia in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 6 publications
(15 reference statements)
0
19
0
Order By: Relevance
“…The wealth of information gathered in the last two decades has shown what structural features are required for the antineoplastic activity exhibited by the quassinoids (3). An A-ring enone function, a C 6 or a C15 ester function, and an oxymethylene bridge between C 8 and C11 or C13 are essential for optimal activity.…”
mentioning
confidence: 99%
“…The wealth of information gathered in the last two decades has shown what structural features are required for the antineoplastic activity exhibited by the quassinoids (3). An A-ring enone function, a C 6 or a C15 ester function, and an oxymethylene bridge between C 8 and C11 or C13 are essential for optimal activity.…”
mentioning
confidence: 99%
“…Previous reports on the cytotoxicity of neosergeolide (Silva et al, 2009) demonstrated that, as observed to other quassinoids (Kupchan et al, 1976;Lee et al, 1982;Lumonadio et al, 1991;Imamura et al, 1993;MataGreenwood et al, 2001;Jiang et al, 2008;Lau et al, 2009), it strongly inhibited the proliferation of tumor cells in spite of their histological origin. The present study was designed to evaluate the selectivity of neosergeolide to tumor cells in comparison to normal lymphocytes, and moreover, to elucidate the underlying mechanism of action.…”
Section: Discussionmentioning
confidence: 83%
“…Generation of Brca1 fp/fp p53 fp/fp Cre and p53 fp/fp Cre mice has been described previously 17,18. The mice were in a C57BL/6 and 129/Sv, mixed background.…”
Section: Methodsmentioning
confidence: 99%